Effectiveness and mechanisms of action of Bacillus velezensis GUMHT p116 against major fungal pathogens causing postharvest soft rot in kiwifruit - Xueping Wu; Zhu Li; Jianjun Lin; Zhanmei Li; Minjie Zhou; Minwei Xiang; Youhua Long; Lijuan Peng; Haixia Ding (Postharvest Biology and Technology, 2026)

Effect of DEM and Gravity Field Representation Strategy On Regional Gravity and Height Anomaly Recovery By the Spectral Enhancement Method - Miao Lin; Song Cheng; Minjia Liu; Yuming Shi; Jianjun Zhu (Studia Geophysica et Geodaetica, 2026)

Magnetite-driven food waste conversion toward high-value medium-chain fatty acids production through promoted biological processes and electrochemical environment - Yuyang Long; Changjie Zhu; Xinyue Wu; Jing Hou; Jianjun Zeng; Shu-Lin Wu (Bioresource Technology, 2026)

Tidal-scale observations reveal the event structure of marsh-edge retreat - Yidong Guo; Qian Yu; Yunwei Wang; Hangjie Lin; Jianjun Jia; Sergio Fagherazzi; Cédric G. Fichot (Geomorphology, 2026)

A 300-year anthropogenic record of sterol biomarkers in sediments from mangrove wetland, Dongzhai Harbor, Hainan Island, South China - Gaoen Wu; Jianjun Wang; Xihuang Lin; Yuhong Wang; Wu Men; Liqiang Xu; Xiuhua Yan; Shihua Han; Guangle Qiu; Manyu Kang; Shuh-Ji Kao (Estuarine, Coastal and Shelf Science, 2026)

Effects of different stand densities and pruning on timber volume and ecosystem carbon sink in subtropical secondary forests: A Case study from Zhejiang Province, China - Xiaomei Jiang; Xiaohong Wu; Suyun Zheng; Weiqing Qiu; Guojun Miao; Jianjun Zhong; Lin Xu; Yongjun Shi (Forest Ecology and Management, 2026)

Impact of the sea surface temperature front over the northern South China Sea on low cloud transition: an observational and numerical case study - Jingchao Long; Jinghong Lin; Shuqi Zhuang; Lingjing Zhu; Jing Luo; Zihan Xie; Yang Chen; Jianjun Xu (Climate Dynamics, 2026)

Global lactylation is downregulated despite lactate accumulation: lactylome data and functional insights during ISKNV infection - Zhourui Sun; Yinjie Niu; Xiaozhe Fu; Qiang Lin; Xianglin Cao; Hongru Liang; Xia Luo; Baofu Ma; Wenwen Xiao; Ningqiu Li; Jianjun Chen (Fish & Shellfish Immunology, 2026)

A constitutive model incorporating particle breakage and strain rate effects for carbonate sand subjected to dynamic loading - Jianjun Ma; Yize Kang; Yilin Gui; Weizhen Huang; Linchong Huang; Yuexiang Lin (Computers and Geotechnics, 2026)

SCR catalysts for municipal solid waste incineration: deactivation mechanisms and poisoning resistance - Jiaqi Li; Wanjia Lin; Junxiao Wei; Hui Liu; Yunjing Xie; Jianjun Cai; Zhong Lin (Clean Technologies and Environmental Policy, 2026)

Moderate net-chasing enhances stress resilience in freshwater prawns Macrobrachium rosenbergii: evidence from behavioral and physiological recovery - Jiangtao Li; Jiale Zhou; Licheng Zeng; Yingtong Ou; Zhongjie You; Zheng Xiao; Jianjun Guo; Li Lin; Xiaojing Lv (Aquaculture, 2026)

Advancements and future perspectives in blueberry processing technology - Jianjun Guo; Xihong Li; Lijun Lin; Beibei Zhang; Yudian Xu; Piao Zhou; Xin Xu (Food and Humanity, 2026)

Bridging accelerated cell-level degradation to module-relevant failure mechanisms in TOPCon solar cells and modules - Xinyuan Wu; Wei Wu; Weiguang Yang; Yan Zhang; Jiexi Fu; Xutao Wang; Jing Yuan; Jianjun Nie; Zhencong Qiao; Chao An; Feng Li; Lin Lv; et al. (Chemical Engineering Journal, 2026)

Analysis of Physical Driving Factors for Long-Term Evolution of Chlorophyll a Concentration in the South China Sea - Caiqin He; Guodong Ye; Chunqiao Lin; Xirui Xu; Hongbo Deng; Weiying Gong; Jianjun Xu; Lingli Fan (Journal of Marine Science and Engineering, 2026)
In the context of global warming, the South China Sea is showing an accelerating warming trend, which highlights the impact of climate change on the marine environment of the South China Sea. The interdecadal variation of chlorophyll a concentration (Chl_a) directly reflects the long-term evolution pattern of the upper marine ecological environment in the South China Sea and has significant indicative significance for marine ecological protection. This study investigated the relationships between Chl_a concentration, sea surface temperature (SST), shortwave radiation (SSRD), mixed layer depth (MLD), wind speed (Wind), and geostrophic current (ugo) in the South China Sea over the past 27 years. Statistical methods were used to analyze the differentiated impacts of marine environmental factors under different climate backgrounds on Chl_a concentration. From 1998 to 2007 (P1), there was a decreasing trend in the early stage, from 2007 to 2015 (P2), there was an upward trend in the middle period, and from 2015 to 2024 (P3), there was an upward trend in the recent period. During these three stages, SST and MLD were the core influencing factors. The threshold of SST gradually increased over time, reaching 27.05 °C, 27.24 °C, and 27.32 °C, respectively. The average normalized information flow (NIF) of Chl_a concentration changed from positive to negative. In the early stage of P1, the SST in most areas of the South China Sea was less than 27.05 °C, and in the P2 and P3 periods, the SST in most areas reached the threshold. The thresholds of MLD were 22.33 m, 21.64 m, and 33.68 m, respectively. The average NIF of Chl_a concentration was positive in all periods. The MLD in most areas of the South China Sea did not reach the threshold in all three periods. These findings emphasize the different roles of marine environmental factors in regulating Chl_a concentration in the South China Sea, providing a scientific basis for the ecological health monitoring of marine fishery areas, disaster warning, and adaptive management in response to climate warming.

Alternaria alternata and its mycotoxins: Sources, toxicological analysis, and control strategies - Xinyue Zhang; Feng Ye; Chenxi Yang; Yingying Zhang; Yujie Zhong; Yueting Sun; Shixin Liu; Xiaoyue Xiao; Qin Wu; Huan Liu; Yongshu Li; Jianjun Hou; et al. (Trends in Food Science & Technology, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Fe/Cu-γ-Al2O3 catalyst for pilot-scale internal circulation Fenton degradation of methyl orange: performance and mechanism - Dekai Fan; Yanran Lin; Peng Zhu; Yingwen Zhang; Bang Yao; Li Chao; Zhuangzhuang Jia; Jianjun Dai; Yingrui Ning; Rong Xiao; Chen Chen; Lei Gao; et al. (Journal of Environmental Management, 2026)

Dark sky protection in high-density urban fringe areas: Site suitability assessment for dark sky parks and light environment optimization strategies—a case study of Guangzhou - Benyan Jiang; Kailing Xu; Zihao Zheng; Jianjun Li; Hongguang Wang; Lin Mei (Journal of Environmental Management, 2026)

The synergistic effects of ammonium and phosphorus on higher alcohol biosynthesis in Zygosaccharomyces mellis LGL-1 and its application for wampee/grape winemaking - Chunyun Qu; Zuyue Qi; Shuochun Lin; Jianjun Li; Yu Zeng; Yiyin Xu; Weidong Bai; Gongliang Liu (Food Microbiology, 2026)

Low accumulation crop rotations enhance safe yields and cadmium drawdown in severely polluted farmland - Jianbin Deng; Yusong Dai; Qijun Zhang; Fangjie Shi; Wenyan Li; Jinjin Wang; Jianjun Zhang; Yongtao Li; Xueming Lin; Yulong Zhang (Agriculture, Ecosystems & Environment, 2026)

Japanese eel SOCS1 suppresses MyD88-mediated NF-κB activation: implications for negative regulation of innate immunity in teleosts - Tianyu Wang; Peng Lin; Yilei Wang; Luis O.B. Afonso; Jianjun Feng (Fish & Shellfish Immunology, 2026)

Toward circular plastic economy: Conversion of marine waste PET into sustainable bio-based polyesters with carbon negative emissions - Hongtao Ning; Qian Ding; Qiang Zhang; Guiquan Liao; Yujun Chen; Qian Liu; Xiaoqiong Xie; Shimei Xu; Lin Chen; Yu-Zhong Wang; Bo Wu; Jianjun Li (Chemical Engineering Journal, 2026)

A Coupled Elastic–Viscoplasticity–Damage Model for Porous Rocks Within Thermodynamic Framework - Jianjun Ma; Weizhen Huang; Yuexiang Lin; Linchong Huang (Rock Mechanics and Rock Engineering, 2026)

Reduction mediated iodide antioxidation: “Chemical Preservation” of precursor solution facilitates construction of high efficiency and stable wide bandgap inverted perovskite solar cells - Chao Liu; Yingchen Li; Hongkun Cai; Boyan Li; Shuping Lin; Qi Sun; Dalong Zhong; Jifeng Liu; Qinwen Guo; Zhiwen Xu; Juan Li; Jian Ni; et al. (Chemical Engineering Journal, 2026)

Chemical characteristics and source apportionment of free amino acids in the Qinling forest atmosphere of central China - Xin Zhang; Rui Wang; Jianjun Li; Shuyan Xing; Lijuan Li; Yue Lin; Junji Cao; Yuemei Han (Atmospheric Environment, 2026)

Shen-Ling-Bai-Zhu-San alleviates ulcerative colitis by enhancing mitophagy via the Nrf2/PINK1/Parkin pathway - Huan Wang; Jian Han; Lin Li; Yan Li; Jun Yang; Wangzhong Qiu; Liuhua Yao; Jianjun Zhou (Journal of Molecular Histology, 2026)

Genome-wide methylation and transcriptome analysis in koi carp (Cyprinus carpio var. koi): Uncovering novel molecular mechanisms in skin color differentiation and pigmentation - Xiulan Shi; Xiaoyu Chen; Wenbin Zhu; Jun Guo; Kai Lin; Jianjun Fu; Lanmei Wang; Mingkun Luo; Zaijie Dong (Aquaculture, 2026)

Microbial community dynamics and its relationship with biogeochemical processes under geochemical perturbations - Jingli Ren; Jianjun Wang; Yiran Dong; Lin Xiao; Lei Wang; Junfeng Ji; Yuanyuan Liu (Water Research, 2026)

The impact of maternal dietary supplementation with lysozyme oligomer on farrowing performance and placental inflammation in sows - Liudan Liu; Xuexun Feng; Huining Liu; Lin Zhou; Wenjia Wei; Yiming Huang; Runchao Huang; Cui Liu; Cuifeng Yin; Chengyu Wu; Jianjun Zuo; Chengquan Tan (Theriogenology, 2026)

An automated and intelligent monitoring system for shield tunneling muck evaluation integrating multimodal data - Zeyu Yue; Linchong Huang; Yuexiang Lin; Yu Liang; Mingfeng Lei; Jianjun Ma (Journal of Cleaner Production, 2026)

Topographic constraints on the rock avalanche erosion mechanisms and sliding effects - Qiyi Lai; Jianjun Zhao; Mengming Lin; Rui Zhang; Chang Yang; Qingmiao Li; Jianxian He (Geomorphology, 2026)

Geothermal hydrogeochemical conditions and genesis of the Mianhuakeng uranium deposit, South China - Siqi Wang; Xiting Long; Jianjun Hu; Feng Liu; Jingyu Lin (Geothermics, 2026)

Associations of Iron Indicators with Cognitive Impairment Risk in Postmenopausal Women: Evidence from a Matched Case–Control Study and Back Propagation Neural Network Model - Wanting Chao; Peiyi Liu; Junyu Li; Yudan Hao; Huijun Zhou; Lijie Feng; Shasha Ruan; Xifei Yang; Jianjun Liu; Yankui Lin; Xian Wang (Molecular Neurobiology, 2026)

Seismic response of subsea shield tunnel under obliquely incident waves: considering cyclic stiffness degradation for marine clays - Weizhen Huang; Kunyue Shen; Jianjun Ma; Yuexiang Lin; Cong He; Weiyun Chen; Linchong Huang (Ocean Engineering, 2025)

Magnetic activated biochar prepared via a novel iron-loading method for efficient lead adsorption and recyclability - Li Chao; Bang Yao; Chenglong Liu; Yang Liu; Chunbao Zhou; Yingwen Zhang; Dekai Fan; Yunxiang Li; Pengfei Zhu; Wei Li; Yanran Lin; Jing Li; et al. (Journal of Environmental Chemical Engineering, 2025)

Molecular characteristics of brown carbon aerosols over a forest atmosphere in the Qinling region of central China - Xin Zhang; Shuyan Xing; Jianjun Li; Rui Wang; Lijuan Li; Yue Lin; Junji Cao; Yuemei Han (Environmental Pollution, 2025)

Construction of high-strength multifunctional flexible sensors based on hydrophobic aggregation phase separation induced by differences in aggregation rate - Jianjun Chen; Xinyi Xiong; Ning Yu; Anqiang Zhang; Yaling Lin (Chemical Engineering Journal, 2025)

Pipeline-pulse electrocoagulation coupled with gravity-driven ceramic membrane for microplastic-laden rainwater purification: Floc structure evolution and interface interaction mechanism - Xing Du; Jiawan Li; Jianjun Liao; Zhitao Zhang; Wei Song; Dachao Lin; Jing Zhao; Qi Song; Zhihong Wang (Chemical Engineering Journal, 2025)

Enhancing polymorphic purity by inducing specific pre-assembled dimer and reducing template particle size - Ke Zhang; Huina Liu; Yan Miao; Zezhi Lin; Liqin Hu; Yingran Duan; Yuan Gao; Jianjun Zhang; Yuanfeng Wei; Shuai Qian (Chemical Engineering Journal, 2025)

Can delivery riders act as informal guardians in crime prevention? - Shuli Zhou; Lin Liu; Han Yue; Kaiyin Yang; Jianjun Li; Guangwen Song (Applied Geography, 2025)

First report of Neopestalotiopsis terricola causing leaf spot disease on Rhododendron fortunei in China - Xiaoli Li; Yingling Huang; Qijiang Wei; Jianjun Lin; Lijuan Peng; Haixia Ding (Crop Protection, 2025)

Preparation of porous thermoresponsive coating (PU@AC-Al) and its synergistic mechanism of early fire warning and flame retardancy - Ting Wang; Wei Lu; Jinliang Li; Jinhu Li; Ao Gao; Jianjun Lin (Process Safety and Environmental Protection, 2025)

Performance and mechanism of double S-scheme FeOOH/TiO2/g-C3N4 heterojunction for acetochlor degradation under visible-light-driven photo-Fenton - Jing Zhang; Xinlei Zhu; Tao Lin; Jianjun Liang (Environmental Research, 2025)

Spin-polarization-enhanced photoreforming of plastic waste - Nan Zhou; Mai Zhang; Shiwei Lin; Linlin Zhang; Jianjun Liao; Chen Li; Wei Zhou (Chemical Engineering Journal, 2025)

Materials and duration of mulching mediate soil and fruit quality in citrus orchard - Lei Yang; Min Wang; Jianjun Yu; Shuang Li; Haihong Tan; Yang Chen; Juhong Liu; Sijia Ye; Jinhui He; Lin Hong (Plant and Soil, 2025)

Genome-based screening and immunogenicity evaluation of outer membrane protein antigens for Vibrio harveyi subunit vaccine in pearl gentian grouper (Epinephelus lanceolatus × Epinephelus fuscoguttatus) - Fuyan Li; Hui Ge; Peng Lin; Yilei Wang; Yonghua Jiang; Ziping Zhang; Yun Chen; Jianjun Feng (Fish & Shellfish Immunology, 2025)

Comparative genome and transcriptome analysis reveals pathogenic mechanisms of Neoscytalidium dimidiatum in pitaya - Shanyu Lin; Jinling Huang; Jianjun Jiang; Junjie Li; Liping Qin; Xiuhong Lu (Physiological and Molecular Plant Pathology, 2025)

Combined oxybenzone and UVB exposure induces metabolic and neural dysregulation in Mugilogobius chulae embryos and larvae - Yimeng Wang; Jinzhi Ren; Yufei Zhao; Xiangping Nie; Ying Peng; Jin Zeng; Yuting Lin; Caixia Gao; Suqun Lai; Jianjun Li (Journal of Hazardous Materials, 2025)

Organ-specific lithium accumulation and its toxic effects on female reproduction - Qigang Fan; Yi Sun; Qingjun Shen; Yuxin Wang; Jisheng Nie; Yanbing Lin; Shuaishuai Xing; Yan Li; Benhong Xu; Jianjun Liu; Xiaoting Shen; Guangbo Qu; et al. (Journal of Hazardous Materials, 2025)

Benzo(a)pyrene-loaded gypsum dust-induced apoptosis of human bronchial epithelial cells through the Ahr signaling pathway - Yujun Wang; Juan Song; Qingqing Lin; Zhenzhen Lv; Faqin Dong; Jianjun Deng (Molecular & Cellular Toxicology, 2025)

Dose-response pattern of marine macroalgae Gracilariopsis heteroclada to three fluoroquinolones and the cause-effect relationship of dose, growth, toxicity and sorption - Kun Lin; Youyou Guo; Rong Xin; Enyi Xie; Xuefeng Wang; Jianjun Cui; Jinhui Wu; Zhaowei Huang; Yong Liu; Shaoliang Lyu; Sipan Wang; Yongjian Huang; et al. (Algal Research, 2025)

A new approach to color correction and equalization for generating mars global color image mosaics from Tianwen-1 MoRIC images - Xin Ren; Xiaoxia Zhang; Wangli Chen; Wei Yan; Xingguo Zeng; Xu Tan; Xingye Gao; Qiang Fu; Lin Guo; Qing Zhang; Zhaopeng Chen; Guobin Yu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Unravelling the pathogenesis of Vibrio parahaemolyticus infection: impacts on antioxidant and innate immunity gene responses in Scylla paramamosain - Guangxin Liu; Ce Li; Sigang Fan; Hongling Ma; Yiqin Deng; Jianjun Jiang; Changhong Cheng; Juan Feng; Li Lin; Zhendong Qin; Zhixun Guo (Fish & Shellfish Immunology, 2025)

Multifunctional motion sensor for health monitoring and treating movement disorders: Construction of tough and elastic multiphase hydrogel based on nanoparticle-micelle synergistic interfacial crosslinking strategy - Jianjun Chen; Ning Yu; Anqiang Zhang; Yaling Lin (Chemical Engineering Journal, 2025)

Microwave-assisted pyrolysis of spent bleaching clay: A study of pyrolysis characteristics, kinetics, and intrinsic mechanism - Bang Yao; Li Chao; Yingwen Zhang; Yang Liu; Chunbao Zhou; Dekai Fan; Yunxiang Li; Pengfei Zhu; Wei Li; Yanran Lin; Lei Gao; Chen Chen; et al. (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Temporal and Spatial changes in flood disaster risk over the past 30 years in the Poyang lake region, China - Bingyu Zhao; Jianjun Wu; Feng Tian; Mengxue Liu; Meng Chen; Jingyu Lin (Natural Hazards, 2025)

An Integrated Safety Monitoring and Pre-Warning System for Fishing Vessels - Kun Yang; Jinglong Lin; Jianjun Ding; Bing Zheng; Li Qin (Journal of Marine Science and Engineering, 2025)
Fishing vessels are essential for the activities of catching, moving, and storing fish. However, fishing vessel accidents claim thousands of deaths every year. This study presents a novel integrated safety monitoring and early warning system designed for fishing vessels, offering significant advancements in maritime safety through real-time alerts based on vessel attitude motion and environmental conditions. The innovation of the system lies in its dual-subsystem architecture: a sensing terminal equipped with a nine-axis sensor, temperature and humidity sensors, a GPS module, and a surveillance camera collects critical data, while a decision support subsystem processes this information via a fuzzy logic-based algorithm to generate a “danger score”. This score quantifies the vessel’s safety status, enabling the system to trigger alerts through SMS and web notifications when predefined thresholds are exceeded. Field trials in the Zhoushan Sea area confirmed the system’s effectiveness in accurately predicting safety hazards and providing timely alerts. The results highlight its potential to enhance operational safety and contribute to the digitization of fisheries management by offering reliable real-time data on vessel conditions. The system’s modular and cost-efficient design ensures it is scalable and adaptable for widespread use across the fishing industry. Our study addresses the limitations of existing technologies by providing a balanced solution that combines comprehensive sensing capabilities with real-time responsiveness and cost-effectiveness, offering a practical and innovative approach to improve fishing vessel safety.

Study on seeding delay time and lag distance of automatic section control system for maize seeder - Lin Ling; Hanqing Li; Yuejin Xiao; Weiqiang Fu; Jianjun Dong; Liwei Li; Rui Liu; Xinguang Huang; Guangwei Wu; Zhijun Meng; Bingxin Yan (Computers and Electronics in Agriculture, 2025)

Pyroptosis was suppressed by 20-hydroxyecdysone through Lin28b-mediated let-7d in vascular endothelial cells - Danli Chen; Jianjun Yang; Lingxuan Ren; Zihan Zheng; Zhen Jin; Jiazheng Wen; Jianyu He; Rongcheng Ding; Jianjiang Wang; Rong Lin; Qiang Song (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

In situ restoration of river sediment by sediment microbial fuel cells enhanced with ecological floating islands - Xiao Li; Jiarui Qi; Jinfeng Zhang; Qinghe Zhang; Qichen Lin; Xiaofeng Li; Jianjun Yu (Journal of Soils and Sediments, 2025)

An arabinogalactan from Lycium barbarum mitigated DSS caused intestinal injury via inhibiting mucosal damage and regulating the gut microbiota disorder - Jiaojiao Mou; Jie Yang; Yanying Sun; Jing Liu; Yuxin Zhao; Hong Lin; Jianjun Yang (Carbohydrate Polymers, 2025)

Exploring the influence of different fillers on the removal process of ammonia and hydrogen sulfide during aerobic composting by establishing deodorization models - Yuanyuan Li; Lin Li; Mengxi Liu; Zehui Zheng; Jianjun Hao; Shuang Liu; Yaya Wang (Journal of Cleaner Production, 2025)

Recycling of flotation residual carbon from coal gasification fine slag through thermal combustion reaction: Insight into the spatial and temporal multi-scale evolution of typical heavy metals - Yang Guo; Jianjun Wu; Fanhui Guo; Yixin Zhang; Shiling Yuan; Chunan Du; Juan Chen; Meng Lin (Fuel, 2025)

FADD cooperates with Caspase-8 to positively regulate the innate immune response and promote apoptosis following bacterial infection in Japanese eel - Tianyu Wang; Peng Lin; Yilei Wang; Yun Chen; Ziping Zhang; Fuyan Li; Jianjun Feng (Fish & Shellfish Immunology, 2025)

Integrated transcriptomic and proteomic analysis unravels the response mechanisms of Saccharina japonica to heat stress - Zhongyuan Lin; Xuelian Liu; Jinbin Lin; Feng Lin; Yijuan Han; Huibin Xu; Hongmei Lin; Weiqi Tang; Yu Qin; Yanbing Zhu; Hui Ni; Jianjun Lu; et al. (Aquaculture, 2025)

Improved anaerobic digestion of food waste under ammonia stress by side-stream hydrogen domestication - Yi Wang; Haoyang Li; Keke Ding; Xueyu Zhao; Miao Liu; Linji Xu; Li Gu; Jinze Li; Lin Li; Qiang He; Jianjun Liang (Water Research, 2025)

Numerical investigations of the mechanical properties and energy characteristics of sandy cobble strata considering its internal stochastic structures - Fan Wang; Pengfei Li; Xiuli Du; Jianjun Ma; Lin Wang (Computers and Geotechnics, 2025)

Modulating the electronic structure of Cu-doped active carbon with high stability via sulfur doping for efficient PH3 removal at low temperature - Yihui He; Lin Ye; Wanglai Cen; Dengrong Sun; Jianjun Li (Chemical Engineering Journal, 2025)

Multi-coal seam mining-induced collapse and deformation evolution of high steep slopes of the Shaomi collapse, Guizhou, China - Baiquan Shen; Weihua Zhao; Jianjun Zhao; Qingmiao Li; Huabo Xiao; Zuoyao Pu; Hanlei Peng; Lin Tan (Landslides, 2025)

Multi-model fusion method for predicting CO2 concentration in greenhouse tomatoes - Jianjun Guo; Beibei Zhang; Lijun Lin; Yudian Xu; Piao Zhou; Shangwen Luo; Yuhan Zhuo; Jingyu Ji; Zhijie Luo; Shahbaz Gul Hassan (Computers and Electronics in Agriculture, 2024)

Effects of relative humidity on atmospheric organosulfur species derived from photooxidation and nocturnal chemistry in a forest environment - Lijuan Li; Jianjun Li; Xin Zhang; Yue Lin; Rui Wang; Junji Cao; Yuemei Han (Environmental Pollution, 2024)

The role of mitochondrial dysfunction in the association between trace metals and QTc prolongation in the aged population - Jiahui Wang; Peiyi Liu; Yankui Lin; Xia Zhang; Lingling Lin; Fengqi Wu; Ying Fu; Desheng Wu; Xiaohu Ren; Haiyan Huang; Xifei Yang; Jianjun Liu (Science of The Total Environment, 2024)

Seasonally inundated area extraction based on long time-series surface water dynamics for improved flood mapping - Bingyu Zhao; Jianjun Wu; Meng Chen; Jingyu Lin; Ruohua Du (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

SOCS6, an inhibitory factor in Japanese eel inhibits the type I IFN pathway and the MyD88-mediated NF-kB pathway - Fuyan Li; Tianyu Wang; Peng Lin; Yilei Wang; Yun Chen; Jianjun Feng (Fish & Shellfish Immunology, 2024)

Pestalotiopsis kenyana causes leaf spot disease on Rhododendron agastum in China - Xiaoli Li; Lingling Liu; Huie Li; Jianjun Lin; Yingping Zuo; Lijuan Peng; Haixia Ding (Crop Protection, 2024)

Effects of photochemical aging on the molecular composition of organic aerosols derived from agricultural biomass burning in whole combustion process - Lijuan Li; Yuemei Han; Jianjun Li; Yue Lin; Xin Zhang; Qiyuan Wang; Junji Cao (Science of The Total Environment, 2024)

Genome sequencing analysis and validation of infestation-related functional genes of Vibrio parahaemolyticus LG2206 isolated from the hepatopancreas of diseased mud crab (Scylla paramamosain) in South China - Liu Guangxin; Liu Guangfeng; Li Ce; Ma Hongling; Deng Yiqin; Cheng Changhong; Jiang Jianjun; Fan Sigang; Feng Juan; Lin Li; Qin Zhendong; Guo Zhixun (Fish & Shellfish Immunology, 2024)

Polystyrene shell-based “coconut-like” and “pomegranate-like” microencapsulated phase change materials: Formation mechanism, thermal conductivity/stability enhancement and their application in thermal management - Wei Zhang; Rui Pan; Jihua Yang; Mengru Liu; Yunle Yao; Awang Zhang; Yi Gong; Zhengya Gan; Rui Hu; Jianjun Ding; Lin Chen; Xian Zhang; et al. (Chemical Engineering Journal, 2024)

Urbanization and carbon emissions in China: Analysis of dynamic relationships from 1978 to 2020 - Zhongyin Wei; Jianjun Tu; Lin Xiao; Wenjing Sun (Journal of Geographical Sciences, 2024)

Genome-wide association study reveals candidate genes critical for skin pigmentation in common carp (Cyprinus carpio) strains including koi - Xiulan Shi; Wenbin Zhu; Jun Guo; Kai Lin; Jianjun Fu; Lanmei Wang; Yalun Dong; Mingkun Luo; Zaijie Dong (Aquaculture, 2024)

Genome-wide identification of SSR markers for Curcuma alismatifolia Gagnep., and their potential for wider application in this genus - Yuanjun Ye; Jianjun Tan; Jingyi Lin; Yu Zhang; Genfa Zhu; Chengrong Nie; Lishan Huang; Yiwei Zhou; Yechun Xu (Journal of Applied Research on Medicinal and Aromatic Plants, 2024)

Lightweight network based on Fourth order Runge-Kutta scheme and Hybrid Attention Module for pig face recognition - Jianjun Guo; Yiyou Kong; Lijun Lin; Longqin Xu; Dachun Feng; Liang Cao; Jiexin Chen; Junwei Ye; Shuqing Ye; Zhaozhong Yao; Yue Liu; Tonglai Liu; et al. (Computers and Electronics in Agriculture, 2024)

Mutual-benefit modification of the coagulant solution and fly ash for enhanced sludge dewatering - Yingfei Sun; Yuexing Wang; Jianjun Zhang; Chengzhi Zhu; Zuohong Chen; Zehui Yu; Bing Li; Ruo-hong Li; Xiao-yan Li; Lin Lin (Chemical Engineering Journal, 2024)

A new subtype of type I IFN receptor, CRFB5b, plays an active role in host antiviral and antibacterial functions in Japanese eel (Anguilla japonica) - Tianyu Wang; Peng Lin; Yilei Wang; Xiaojian Lai; Pengyun Chen; Fuyan Li; Jianjun Feng (Aquaculture International, 2024)

A 76-m per pixel global color image dataset and map of Mars by Tianwen-1 - Jianjun Liu; Xin Ren; Wei Yan; Wangli Chen; Xingguo Zeng; Xiaoxia Zhang; Xu Tan; Xingye Gao; Qiang Fu; Dingxin Liu; Lin Guo; Qing Zhang; et al. (Science Bulletin, 2024)

The effects of impurities in carbide slag on the morphological evolution of CaCO3 during carbonation - Zihe Pan; Chunxia Cao; Bo Wang; Fengjie Zhang; Lin Chen; Jianjun Zhao; Zhien Zhang; Huaigang Cheng (Journal of Environmental Management, 2024)

Toll-interacting protein is activated by the transcription factor GATA1 and Sp1 to negatively regulate NF-κB and MAPK pathways in the Japanese eel (Anguilla japonica) - Tianyu Wang; Hui Ge; Peng Lin; Yilei Wang; Xiaojian Lai; Pengyun Chen; Fuyan Li; Jianjun Feng (Fish & Shellfish Immunology, 2024)

A dual-network structured poly (m-phenylene isophthalamide) nanofiber separator with Li6.4La3Zr1.4Ta0.6O12 for dendrite-free and high-safety lithium-metal batteries - Huijuan Zhao; Guodong Zhao; Fengquan Liu; Feifei Lan; Jianjun Zhou; Lin Li (Chemical Engineering Journal, 2024)

Green synthesis of Fe3O4@ceramsite from sludge improving anaerobic digestion performance of waste activated sludge - Pengqu Zhang; Dongsheng Shen; Jinyang Shao; Xiaoyu He; Jianjun Zeng; Shu-Lin Wu; Yuyang Long; Wei Wei; Bing-Jie Ni (Journal of Environmental Management, 2024)

Lowing surface steric hindrance of strongly-confined perovskite quantum dots enables efficient pure-red light-emitting diodes - Shixu Yang; Jing Li; Junfeng Wang; Lin Zhang; Linhan Fan; Xiong Chen; Fei Huang; Jianjun Tian (Chemical Engineering Journal, 2024)

Responses of arbuscular mycorrhizal fungi to straw return and nitrogen fertilizer reduction in a rainfed maize field - Zhenling PENG; Hao XI; Lin MAO; Huyuan FENG; Jianjun ZHANG; Yongjun LIU (Pedosphere, 2024)

Targeted degradation of Bisphenol A with peroxymonosulfate activated by nanoscale zero-valent iron supported on molecularly imprinted polymers - Xinlei Zhu; Juncheng Ke; Chunyan Hu; Tao Lin; Jianjun Liang (Chemical Engineering Journal, 2024)

Arsenic(III) sorption on organo-ferrihydrite coprecipitates: Insights from maize and rape straw-derived DOM - Aminu Darma; Yichen Liu; Xing Xia; Yihao Wang; Lin Jin; Jianjun Yang (Chemosphere, 2024)

Sediment provenance changes in the southwestern Okhotsk Sea since MIS 5 and their implications for sediment transport dynamics - Anqi Wang; Zhengquan Yao; Xuefa Shi; Kunshan Wang; Yanguang Liu; Jianjun Zou; Yuriy Vasilenko; Fengdeng Shi; Zhi Dong; Xiaojing Wang; Aimei Zhu; Zhengfan Lin; et al. (Global and Planetary Change, 2024)

Well plate-based LF-NMR/colorimetric dual-mode homogeneous immunosensor for Vibrio parahaemolyticus detection - Dongyu Zhang; Le Chen; Han Lin; Tingting Hao; Yangbo Wu; Jianjun Xie; Xizhi Shi; Xiaohua Jiang; Zhiyong Guo (Food Chemistry, 2024)

Influence of speed measurement method on performance of an electric-drive maize precision planter - Lin Ling; Guangwei Wu; Changkai Wen; Yuejin Xiao; Weiqiang Fu; Jianjun Dong; Jianhong Ding; Zhijun Meng; Bingxin Yan (Biosystems Engineering, 2024)

Water stress significantly affects the diurnal variation of solar-induced chlorophyll fluorescence (SIF): A case study for winter wheat - Jingyu Lin; Litao Zhou; Jianjun Wu; Xinyi Han; Bingyu Zhao; Meng Chen; Leizhen Liu (Science of The Total Environment, 2024)

Widely targeted metabolomic analysis reveals the dynamic changes of metabolites during postmortem chilled aging in Mongolian sheep - Min Zhang; Lina Sun; Rina Su; Mirco Corazzin; Zhihao Yang; Lu Dou; Guanhua Hu; Yue Zhang; Ting Liu; Yueying Guo; Lihua Zhao; Lin Su; et al. (Food Chemistry, 2024)

Spatio-temporal variation of toxin-producing gene abundance in Microcystis aeruginosa from Poyang Lake - Lin Wu; Li Zhang; Lijuan Yuan; Qiegen Liao; Jianjun Xiang; Dawen Zhang; Tong Qiu; Jutao Liu; Junhui Guo (Environmental Science and Pollution Research, 2023)

Reservoir horizontal principle stress prediction using intelligent fusion model based on physical model constraints: a case study of Daji Block, Eastern Ordos Basin, North China - Haiyu Lin; Xiangjun Liu; Jian Xiong; Lixi Liang; Jianjun Wu; Bing Li (Acta Geophysica, 2023)

Key decomposers of straw depending on tillage and fertilization - Hao Xi; Mengying Jia; Yakov Kuzyakov; Zhenling Peng; Yali Zhang; Jiayao Han; Gohar Ali; Lin Mao; Jianjun Zhang; Tinglu Fan; Yongjun Liu (Agriculture, Ecosystems & Environment, 2023)

The roles of lipoxygenases and autoxidation during mackerel (Scomberomorus niphonius) dry-cured processing - Qiaoyu Liu; Menglin Lei; Jianjun Lin; Wenhong Zhao; Xiaofang Zeng; Weidong Bai (Food Research International, 2023)

Deep spatiotemporal transcriptome analysis provides new insights into early development of koi carp (Cyprinus carpio var. koi) - Mingkun Luo; Xiulan Shi; Jun Guo; Kai Lin; Wenbin Zhu; Jianjun Fu; Lanmei Wang; Zaijie Dong (Aquaculture, 2023)

Study on Tamped Spherical Detonation-Induced Dynamic Responses of Rock and PMMA Through Mini-chemical Explosion Tests and a Four-Dimensional Lattice Spring Model - Jianjun Ma; Jinxin Zhao; Yuexiang Lin; Jiguan Liang; Junjie Chen; Wanxiang Chen; Linchong Huang (Rock Mechanics and Rock Engineering, 2023)

Climate change-induced shrub encroachment changes soil hydraulic properties and inhibits herbaceous growth in alpine meadows - Yi-Fan Liu; Hui Fang; Jianjun Shi; Pedro A M Leite; Jingxue Zhao; Gao-Lin Wu (Agricultural and Forest Meteorology, 2023)

How do livelihood capital affect farmers' energy-saving behaviors: Evidence from China - Lin Li; Jianjun Jin; Chenyang Zhang; Xin Qiu; Dan Liu (Journal of Cleaner Production, 2023)

Heterogeneous photo-Fenton catalyst α-Fe2O3@g-C3N4@NH2-MIL-101(Fe) with dual Z-Scheme heterojunction for degradation of tetracycline - Chunyan Hu; Jinke He; Jianjun Liang; Tao Lin; Qiuliang Liu (Environmental Research, 2023)

Pexidartinib hydrochloride exposure induces developmental toxicity and immunotoxicity in zebrafish embryos via activation of Wnt signaling - Fasheng Liu; Hongmei Hu; Guilan Chen; Yanqi Lin; Wei Li; Ziyi Liu; Chao Chen; Xue Li; Sujie Sun; Li Zhang; Dou Yang; Kangyu Liu; et al. (Fish & Shellfish Immunology, 2023)

Exploring the effects of livelihood capital on clean cooking of rural households in the Tibetan region of China - Xin Qiu; Jianjun Jin; Chenyang Zhang; Dan Liu; Lin Li; Foyuan Kuang (Energy and Buildings, 2023)

Berberine inhibits the progression of renal cell carcinoma cells by regulating reactive oxygen species generation and inducing DNA damage - Yuwan Zhao; Xinghua Lin; Wenfeng Zeng; Xingzhang Qin; Bailiang Miao; Sheng Gao; Jianjun Liu; Zhuo Li (Molecular Biology Reports, 2023)

Disruption of the ADAM17/NF-κB feedback loop in astrocytes ameliorates HIV-1 Tat-induced inflammatory response and neuronal death - Xiaoxia Qiu; Jianjun Wang; Wei Zhang; Chengwei Duan; Tianpeng Chen; Dongmei Zhang; Jianbin Su; Lin Gao (Journal of NeuroVirology, 2023)

Climate impacts of 2009/2010 mixed-type El Niño on double ITCZs over the eastern Pacific Ocean - Yinlan Chen; Li Yan; Jianjun Xu; Shaojun Zheng; Guihua Chen; Peixian Lin (Frontiers in Marine Science, 2023)
A double intertropical convergence zone (ITCZ) pattern emerges over the eastern Pacific Ocean in March-April. Their inter-annual variabilities may exert major climatic and ecological effects. El Niño-Southern Oscillation (ENSO) can significantly regulate the inter-annual variability of double ITCZs. ENSO diversity has increased in recent years. A mixed-type El Niño occurred in 2009/2010. Our results reveal that the meridional SSTA pattern in mixed-type El Niño is a combination of “SST warming with a maximum at the equator” (i.e., EP-type delta SST) and “north-warm and south-cold” (i.e., CP-type delta SST) patterns. In a mixed-type El Niño, both meridional EP-type and CP-type delta SST played a role and had corresponding climate impacts. Under the coordinated modulation of EP-type and CP-type delta SST in a mixed-type El Niño, the climate effect of EP-type delta SST (increasing equatorial precipitation) is weakened; while the climate effect of CP-type delta SST (enhancing the northern ITCZ and weakening the southern ITCZ) is amplified. The climate effect of mixed-type El Niño finally resembles that of typical CP-type El Niños, intensifying the north-south asymmetry of the eastern Pacific double ITCZs. This study will contribute to a better understanding of the impacts of ENSO diversity on double ITCZs in the eastern Pacific region.

Cluster-bomb type magnetic biosensor for ultrasensitive detection of Vibrio parahaemolyticus based on low field nuclear magnetic resonance - Dongyu Zhang; Han Lin; Le Chen; Yangbo Wu; Jianjun Xie; Xizhi Shi; Zhiyong Guo (Analytica Chimica Acta, 2023)

Reversal of soil moisture constraint on vegetation growth in North China - Ruohua Du; Jianjun Wu; Feng Tian; Jianhua Yang; Xinyi Han; Meng Chen; Bingyu Zhao; Jingyu Lin (Science of The Total Environment, 2023)

Effects of social capital on farmers’ choices of climate change adaptation behavior in Dazu District, China - Lin Li; Jianjun Jin; Rui He; Foyuan Kuang; Chenyang Zhang; Xin Qiu (Climate and Development, 2023)

Hypoxia triggers the proliferation of antibiotic resistance genes in a marine aquaculture system - Yiqin Deng; Jianjun Jiang; Yinbang Huang; Changhong Cheng; Ziyang Lin; Guangxin Liu; Zhixun Guo; Juan Feng (Science of The Total Environment, 2023)

Programmable CRISPR-Cas12a and self-recruiting crRNA assisted dual biosensing platform for simultaneous detection of lung cancer biomarkers hOGG1 and FEN1 - Xia Cheng; Xinyi Xia; Dandan Ren; Qiutong Chen; Guanhong Xu; Fangdi Wei; Jing Yang; Lin Wang; Qin Hu; Jianjun Zou; Yao Cen (Analytica Chimica Acta, 2023)

The dynamic changes of flavors and UPLC-Q-Exactive-Orbitrap-MS based lipidomics in mackerel (Scomberomorus niphonius) during dry-cured processing - Qiaoyu Liu; Jianjun Lin; Wenhong Zhao; Menglin Lei; Juan Yang; Weidong Bai (Food Research International, 2023)

Recycle waste washcloth to design Fe3O4/FeS2/C heterojunction membrane as high-area capacity freestanding anode for sodium-ion batteries - Qing Lin; Shaocheng Zhang; Li-Juan Yu; Baoxiu Hou; Shuaihua Zhang; Zheng Wang; Jianjun Song; Xiaoxian Zhao (Chemical Engineering Journal, 2023)

Effects of Ran-GTP/importin β inhibition on the meiotic division of porcine oocytes - Yijing He; Jia Li; Lei Peng; Qiao Li; Yajie Chu; Qixin Lin; Jianjun Dai; Rong Rui; Shiqiang Ju (Histochemistry and Cell Biology, 2022)

Biological Effect Evaluation of Different Sized Titanium Dioxide Nanoparticles Using Bombyx mori (Silkworm) as a Model Animal - Sandra Senyo Fometu; Qiang Ma; JinJin Wang; Jianjun Guo; Lin Ma; Guohua Wu (Biological Trace Element Research, 2022)

Ginsenoside Rb3 attenuates skin flap ischemia-reperfusion damage by inhibiting STING-IRF3 signaling - Yuanbin Li; Haifen Liu; Zhaohui Zeng; Hui Lin; Xin Chen; Xianglian Yuan; Jizhe Qiu; Fengchun Fu; Zhuang Chen; Jianjun Kuang (Journal of Molecular Histology, 2022)

Effects of micronized bamboo powder on growth performance, serum biochemical indexes, cecal chyme microflora and metabolism of broilers aged 1–22 days - Fawen Dai; Tao Lin; Lumin Cheng; Jian Wang; Jianjun Zuo; Dingyuan Feng (Tropical Animal Health and Production, 2022)
Adding insoluble fiber to diet of broilers has been reported to improve intestinal health and promote growth performance. Bamboo powder is a cheap raw material with rich insoluble fiber. This study aims to explore the effects of feeding micronized bamboo powder (MBP) on growth performance, serum biochemical indexes, intestinal microflora, and metabolism of broilers. A total of 1440 1-day-old slow-growing Ephedra chickens were randomly divided into three groups considering gender and body weight: (1) Group D: feeding with basal diet without antibiotics; (2) Group E: feeding with basal diet supplemented with 5% rice bran (RB); (3) Group F: feeding with basal diet supplemented with 1% MBP. Each group involved 8 replicates feeding for 22 days, with 60 chickens per replicate. Various indexes were detected. For the growth performance, the weight gain and feed consumption ratio (G: F) of Group F supplemented with MBP is 0.57 ± 0.04, which is significantly higher than that of E group supplemented with RB (0.52 ± 0.01, P < 0.05). For the serum biochemical indexes, the glutathione peroxidase activity in Group F is significantly higher than that of Group D, while the malondialdehyde content is significantly lower than that of Group D and Group E ( P < 0.05 for all). The fresh cecal chyme is taken for determination. In Group F, the α diversity index Faith_pd is significantly lower in Group F than that of Group D. The microorganism species in cecal chyme of Group F and Group E are also different. The metabolic pathways of Group F, mainly in fatty acid metabolism, amino acid metabolism and intestinal immune IgA production, were different from those of Group D and Group E. Adding 1% MBP to broiler diet can enhance the anti-oxidant capacity, improve chyme microflora, regulate the metabolism pathways responsible for intestinal fatty acids, amino acids, and immunity.

Soil biota suppress maize growth and influence root traits under continuous monoculture - Lin Mao; Yongjun Liu; Jianjun Zhang; Jessica Okerblad; Senyu Chen; Nancy Collins Johnson (Plant and Soil, 2021)

Association of Circulating and Aortic Zinc and Copper Levels with Clinical Abdominal Aortic Aneurysm: a Meta-analysis - Tingting Chen; Hongliang Zhang; Yang Zhang; Mengqi Yang; Juntao Wu; Minjun Yang; Jiangbo Lin; Weixu Gao; Lijiang Tang; Baohui Xu; Jianjun Jiang; Xiaofeng Chen (Biological Trace Element Research, 2021)

Spectral responsivity calibration of a polarization remote sensor based on a supercontinuum laser and monochromator - Chenyu Xie; Wenchao Zhai; Jianjun Li; Lin Yin; Haoyu Wu; Xiaobing Zheng (International Journal of Remote Sensing, 2020)

Regional eco-efficiency evaluation and spatial pattern analysis of the Yangtze River Economic Zone - Lin Ha; Jianjun Tu; Jianping Yang; Chunhai Xu; Jiaxing Pang; Debin Lu; Zuolin Yao; Wenyu Zhao (Journal of Geographical Sciences, 2020)

Macrobenthic communities on the continental shelf of the Prydz Bay, East Antarctica - Kun Liu; Heshan Lin; Xuebao He; Yaqin Huang; Zhong Li; Junhui Lin; Jianfeng Mou; Shuyi Zhang; Jianjun Wang; Jun Sun (Acta Oceanologica Sinica, 2020)

Geochemical Appraisal of Chemical Weathering and Metal Contamination in Coastal Surface Sediments, Off Northwest Hainan Island, the Gulf of Tonkin - Dawei Liu; Baozhi Lin; Selvaraj Kandasamy; Huawei Wang; Qianqian Liu; Wenbin Zou; Aimei Zhu; Jianjun Zou; Jiann-Yuh Lou; Xuefa Shi (Frontiers in Marine Science, 2019)

Relationship between warfarin dosage and international normalized ratio: a dose–response analysis and evaluation based on multicenter data - Ling Xue; Yuzhen Zhang; Cheng Xie; Ling Zhou; Linsheng Liu; Haiyan Zhang; Lianhong Xu; Hongtao Song; Meiqin Lin; Hanfan Qiu; Junrong Zhu; Yubing Zhu; et al. (European Journal of Clinical Pharmacology, 2019)

Spatial variability of macrobenthic production in the Bering Sea - Heshan Lin; Kun Liu; Jianjun Wang; Junhui Lin; Yaqin Huang; Xuebao He; Zhong Li; Shuyi Zhang; Jianfeng Mou; Yanguang Liu; Puqing Song; Yu Wang; et al. (Polar Biology, 2019)

Year-round records of bulk aerosol composition over the Zhongshan Station, Coastal East Antarctica - Guojie Xu; Liqi Chen; Miming Zhang; Yuanhui Zhang; Jianjun Wang; Qi Lin (Air Quality, Atmosphere & Health, 2019)

The contribution of parent-to-offspring transmission of telomeres to the heritability of telomere length in humans - Dayana A. Delgado; Chenan Zhang; Kevin Gleason; Kathryn Demanelis; Lin S. Chen; Jianjun Gao; Shantanu Roy; Justin Shinkle; Mekala Sabarinathan; Maria Argos; Lin Tong; Alauddin Ahmed; et al. (Human Genetics, 2019)

Mediomastus chinensis sp. nov., a new species of Capitellidae (Annelida: Polychaeta) from the southeast coast of China - Junhui Lin; Jianjun Wang; Fengwu Zheng (Acta Oceanologica Sinica, 2018)

Spatial pattern of macrobenthic communities along a shelf-slope-basin transect across the Bering Sea - Heshan Lin; Kun Liu; Jianjun Wang; Yaqin Huang; Zhong Li; Junhui Lin; Xuebao He; Shuyi Zhang; Jianfeng Mou; Yu Wang; Bingpeng Xing (Acta Oceanologica Sinica, 2018)

An ecological survey of the abundance and diversity of benthic macrofauna in Indonesian multispecific seagrass beds - Junhui Lin; Yaqin Huang; Ucu Yanu Arbi; Heshan Lin; Muhammad Husni Azkab; Jianjun Wang; Xuebao He; Jianfeng Mou; Kun Liu; Shuyi Zhang (Acta Oceanologica Sinica, 2018)

Avulsions in a Simulated Large Lowland Braided River - Haiyan Yang; Binliang Lin; Jianjun Zhou (Water Resources Management, 2018)

Size structure of biomass and primary production of phytoplankton: environmental impact analysis in the Dongsha natural gas hydrate zone, northern South China Sea - Jianhua Kang; Qianyong Liang; Jianjun Wang; Yili Lin; Xuebao He; Zhen Xia; Xinqing Zheng; Yu Wang (Acta Oceanologica Sinica, 2018)

Influences of meteorological conditions on interannual variations of particulate matter pollution during winter in the Beijing–Tianjin–Hebei area - Jianjun He; Sunling Gong; Hongli Liu; Xingqin An; Ye Yu; Suping Zhao; Lin Wu; Congbo Song; Chunhong Zhou; Jie Wang; Chengmei Yin; Lijuan Yu (Journal of Meteorological Research, 2017)

Fouling community characteristics in subtropical coastal waters of the southwestern East China Sea - Heshan Lin; Jianjun Wang; Wei Liu; Kun Liu; Shuyi Zhang; Xuebao He; Yaqin Huang; Junhui Lin; Jianfeng Mou; Chengxing Zheng; Tao Yan (Acta Oceanologica Sinica, 2017)

Novel avian leukosis viruses from domestic chicken breeds in mainland China - Hongxia Shao; Lin Wang; Jianjun Sang; Tuofan Li; Yuelong Liu; Zhimin Wan; Kun Qian; Aijian Qin; Jianqiang Ye (Archives of Virology, 2017)

Protective Effects of Extracellular and Intracellular Polysaccharides on Hepatotoxicity by Hericium erinaceus SG-02 - Fangyuan Cui; Xia Gao; Jianjun Zhang; Min Liu; Chen Zhang; Nuo Xu; Huajie Zhao; Lin Lin; Meng Zhou; Le Jia (Current Microbiology, 2016)

Numerical Model-Based Artificial Neural Network Model and Its Application for Quantifying Impact Factors of Urban Air Quality - Jianjun He; Ye Yu; Yaochen Xie; Hongjun Mao; Lin Wu; Na Liu; Suping Zhao (Water, Air, & Soil Pollution, 2016)

A new deep-sea hydroid (Cnidaria: Hydrozoa) from the Bering Sea Basin reveals high genetic relevance to Arctic and adjacent shallow-water species - Xikun Song; Cinzia Gravili; Jianjun Wang; Yacheng Deng; Yongqiang Wang; Lu Fang; Heshan Lin; Shaoqing Wang; Yiting Zheng; Junhui Lin (Polar Biology, 2016)

Characterization of resistance to multiple fungicides in Botrytis cinerea populations from Asian ginseng in northeastern China - Xiao Hong Lu; Xiao Lin Jiao; Jianjun J. Hao; Amanda Juan Chen; Wei Wei Gao (European Journal of Plant Pathology, 2016)

Isolation and sequence analysis of a canine distemper virus from a raccoon dog in Jilin Province, China - Yuening Cheng; Jianke Wang; Miao Zhang; Jianjun Zhao; Xiqun Shao; Zengjun Ma; Hang Zhao; Peng Lin; Hua Wu (Virus Genes, 2015)

Quantitative trait locus analysis and fine mapping of the qPL6 locus for panicle length in rice - Lin Zhang; Jianjun Wang; Junmin Wang; Linyou Wang; Bin Ma; Longjun Zeng; Yongbin Qi; Qun Li; Zuhua He (Theoretical and Applied Genetics, 2015)

Dissipation of phenanthrene and pyrene at the aerobic–anaerobic soil interface: differentiation induced by the rhizosphere of PAH-tolerant and PAH-sensitive rice (Oryza sativa L.) cultivars - Yan He; Wen Xia; Xinfeng Li; Jiajiang Lin; Jianjun Wu; Jianming Xu (Environmental Science and Pollution Research, 2015)

Epigenetic Enhancement of Brain-Derived Neurotrophic Factor Signaling Pathway Improves Cognitive Impairments Induced by Isoflurane Exposure in Aged Rats - MuHuo Ji; Lin Dong; Min Jia; WenXue Liu; MingQiang Zhang; LinSha Ju; JiaoJiao Yang; Zhongcong Xie; JianJun Yang (Molecular Neurobiology, 2014)

Impact of meteorological drought on streamflow drought in Jinghe River Basin of China - Lin Zhao; Aifeng Lyu; Jianjun Wu; Michael Hayes; Zhenghong Tang; Bin He; Jinghui Liu; Ming Liu (Chinese Geographical Science, 2014)

Biodiversity and community structural characteristics of macrobenthos in the Chukchi Sea - Jianjun Wang; Heshan Lin; Xuebao He; Junhui Lin; Yaqin Huang; Rongguan Li; Chengxing Zheng; Fengwu Zheng; Jinxiang Jiang (Acta Oceanologica Sinica, 2014)

Community structure and spatial distribution of macrobenthos in the shelf area of the Bering Sea - Jianjun Wang; Xuebao He; Heshan Lin; Junhui Lin; Yaqin Huang; Chengxing Zheng; Fengwu Zheng; Rongguan Li; Jinxiang Jiang (Acta Oceanologica Sinica, 2014)

miR-27b targets LIMK1 to inhibit growth and invasion of NSCLC cells - Li Wan; Lin Zhang; Kai Fan; Jianjun Wang (Molecular and Cellular Biochemistry, 2014)

Quantitative assessment and spatial characteristic analysis of agricultural drought risk in China - Bin He; Jianjun Wu; Aifeng Lü; Xuefeng Cui; Lei Zhou; Ming Liu; Lin Zhao (Natural Hazards, 2013)

Neural correlates of stimulus spatial frequency-dependent contrast detection - Jianjun Meng; Ruilong Liu; Ke Wang; Tianmiao Hua; Zhong-Lin Lu; Minmin Xi (Experimental Brain Research, 2013)

Regional differences in the relationship between climatic factors, vegetation, land surface conditions, and dust weather in China’s Beijing-Tianjin Sand Source Region - Jianjun Wu; Lin Zhao; Yanting Zheng; Aifeng Lü (Natural Hazards, 2012)

Comparison of remotely sensed and meteorological data-derived drought indices in mid-eastern China - Lei Zhou; Jie Zhang; Jianjun Wu; Lin Zhao; Ming Liu; Aifeng Lü; Zhitao Wu (International Journal of Remote Sensing, 2012)

Mechanism of Monoclonal Antibody-Coupled Staphylococcus Superantigen-A Induced Apoptosis in Human Bladder Cancer Cells - Conghui Han; Zhen Gong; Lin Hao; Jianjun Yang; Jianpeng Hu; Bingzheng Dong; Tao Fan; Wenhao Tang; Gaojun Teng (Cell Biochemistry and Biophysics, 2011)

Drought hazard assessment and spatial characteristics analysis in China - Bin He; Aifeng Lü; Jianjun Wu; Lin Zhao; Ming Liu (Journal of Geographical Sciences, 2011)

Quantitative assessment and spatial characteristics analysis of agricultural drought vulnerability in China - Jianjun Wu; Bin He; Aifeng Lü; Lei Zhou; Ming Liu; Lin Zhao (Natural Hazards, 2011)

Effects of plant types on physico-chemical properties of reclaimed mining soil in Inner Mongolia, China - Yao Fu; Changcun Lin; Jianjun Ma; Tingcheng Zhu (Chinese Geographical Science, 2010)

Speciation and biochemical transformations of sulfur and copper in rice rhizosphere and bulk soil—XANES evidence of sulfur and copper associations - Huirong Lin; Jiyan Shi; Bei Wu; Jianjun Yang; Yingxu Chen; Yidong Zhao; Tiandou Hu (Journal of Soils and Sediments, 2010)

Borealin is differentially expressed in ES cells and is essential for the early development of embryonic cells - Qianjun Zhang; Ge Lin; Yifang Gu; Jianjun Peng; Zaoyan Nie; Yuelong Huang; Guangxiu Lu (Molecular Biology Reports, 2009)

Fourteen FITC-conjugated lectins as a tool for the recognition and differentiation of some harmful algae in Chinese coastal waters - Jianjun Hou; Bangqin Huang; Jun Hu; Lizhen Lin; Huasheng Hong (Journal of Applied Phycology, 2008)

A locus for familial generalized lentiginosis without systemic involvement maps to chromosome 4q21.1–q22.3 - Qinghe Xing; Xiangdong Chen; Mingtai Wang; Wenjie Bai; Xin Peng; Rui Gao; Shengnan Wu; Xueqing Qian; Wei Qin; Jianjun Gao; Guoyin Feng; Lin He (Human Genetics, 2005)